1995
DOI: 10.1677/joe.0.1440143
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of receptors for prolactin in ovine skin

Abstract: Although prolactin (PRL) receptors are found in many mammalian tissues, specific PRL binding to mammalian skin has not been demonstrated. In view of the temporal relationships observed between photoperiod, circulating PRL and pelage replacement in seasonally responsive mammals, we sought to provide evidence of PRL receptors in ovine skin. Cryosections of skin from New Zealand Wiltshire ewes were incubated with radiolabelled human GH (125I-hGH) and ovine PRL (125I-oPRL) in the presence and absence of excess unl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
1
10
1
Order By: Relevance
“…Although PRL protein expression in murine hair follicles has not been previously reported, other studies have shown that PRLR RNA is localized in the epidermis, skin glands, ORS, and DP of ovine anagen hair follicles. 34,35,47 In contrast to studies in sheep, we could detect the PRLR only in follicular epithelial cells and it was notably absent from the DP, connective tissue sheath, and sebaceous gland. These findings were partially consistent with those of Craven and colleagues, 15 who found PRLR staining in the epidermis, sebaceous gland, and ORS of the hair follicle, but not in the DP of murine anagen hair follicles.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although PRL protein expression in murine hair follicles has not been previously reported, other studies have shown that PRLR RNA is localized in the epidermis, skin glands, ORS, and DP of ovine anagen hair follicles. 34,35,47 In contrast to studies in sheep, we could detect the PRLR only in follicular epithelial cells and it was notably absent from the DP, connective tissue sheath, and sebaceous gland. These findings were partially consistent with those of Craven and colleagues, 15 who found PRLR staining in the epidermis, sebaceous gland, and ORS of the hair follicle, but not in the DP of murine anagen hair follicles.…”
Section: Discussioncontrasting
confidence: 99%
“…31 And although PRL is incapable of binding to the receptors for GH, it has somatotrophic activity in rodents. 32 PRLRs have been shown to be expressed in epidermal keratinocytes in humans, 33 in the wool follicles of sheep, 34,35 and anagen hair follicles of mice 15 suggesting that PRL operates directly on the skin.…”
mentioning
confidence: 99%
“…These in situ hybridisation data concur with earlier receptor protein localisation (Choy et al 1995(Choy et al , 1997). As noted above, migration of clonogenic cells from the outer root sheath has been implicated in cycle control (Oshima et al 2001).…”
Section: Discussionsupporting
confidence: 90%
“…Fibre growth can be altered by either local injection (Thomas et al 1994) or systemic prolactin treatments (Pearson et al 1999). Prolactin receptors (PRLR) have been detected in skin by in situ hybridisation (Ouhtit et al 1993), radioligand binding (Choy et al 1995) and immunocytochemistry (Choy et al 1997, Craven et al 2001. Interestingly, PRLR localise particularly to the outer root sheaths and dermal papillae of hair follicles.…”
Section: Introductionmentioning
confidence: 99%
“…This feature plays an important role in the regulation of these systems by producing binding surfaces with dramatically different binding affinities to the receptor. 35 Such PRL-R are expressed by human epidermal keratinocytes in vitro 36 ; in the dermal papilla, matrix, outer root sheath, lower regions of the inner root sheath, and connective tissue sheath in wool follicles of sheep 37,38 ; and in the outer root sheath of anagen HFs of mice. 22,23 This expression pattern suggests that PRL can directly alter skin and HF functions by targeting cognate, locally expressed receptors.…”
mentioning
confidence: 99%